Understanding of people with spinal cord injury about the performance of transfers for their daily activities (Revista Contexto & Saúde, 2026)
Objective: to understand, based on the Adaptation Model, how people with spinal cord injury perceive and perform safe transfers in their daily activities. Methodology: qualitative study, based on the Adaptation Model. A total of 17 paraplegics with post-traumatic spinal cord injury were interviewed. The participants’ information was analyzed in light of content analysis. Results: of the 17 participants, 15 men and 2 women, only 11 declared themselves as rehabilitated; in fact, eight stated that they had not received training to perform transfers. The analysis of the raw data was decoded into recording units, which gave rise to two thematic categories: “Essential adaptive skills that distinguish them as dependent or independent for the performance of daily activities” and “Activities that promote autonomy and restore self-confidence, either from the received training or through peer sharing.” Final Considerations: the participants stated that performing transfers safely and independently is crucial for them to carry out their daily activities with autonomy, functional independence, leave the house, and achieve full social inclusion. They also reported that they share experiences with peers and use resources of new learning available on social networks. In this way, nurses specialized in rehabilitation, based on the Adaptation Model, can invest in guidance, training, and periodic assessment of transfers, to minimize the daily difficulties of people with spinal cord injury, since they work in the direct care of these people in the various spheres of health care, aiming at the promotion of their self-esteem, adaptation, and independent life.
Keywords: Assistive Technology; Daily Activities; Spinal Cord Injury; International Classification of Functioning; Disability and Health; Rehabilitation Nursing